Natação sob a perspectiva da epistemologia da complexidade: uma prática criativa de transcendência de atletas com deficiência - Sobral, Anna Clara Souza (2023)
The aim of this research is to investigate swimming from the perspective of complexity theory, looking at swimming for athletes with disabilities as a way for the recognition of the creative subject and for transcendence. The line of research is Education, School and Technology. The problematizing question is: does swimming, through the pedagogical practices of its teachers, contribute to the transcendence of athletes with disabilities? The general objective: To analyze whether swimming can contribute to the transcendence of athletes with disabilities. It unfolds into three specific objectives: 1. Investigate what is the transcendence of being a disabled athlete; 2. Recognize the creative and integral subject through complex thinking; 3. Search athletes from Associação Paralímpica do Futuro for reports about swimming. The main authors that we will use are: M. D. Alves (2015), O. Andries Junior (2008), G. Bachelard (1998), Y. Berge (1986), E. Kunz (2015), M. C. Moraes (2004), E. Morin (2003, 2015, 2010), J. H. S. Suanno (2014) and La Torre (2004). The methodological flow aimed at unveiling the problem is through qualitative research, embracing exploratory paths to study the object. The choice of interview technique is closer to the objective proposed in the project and consisted of seven open questions, prioritizing the experience and spontaneity of the participants, considering emotions, perceptions and feelings about the importance of aquatic practices in their lives. Through the athletes' speeches, it is seen that swimming expands in all senses, be they social, physical and psychic, in addition to social interaction, beyond just swimming from one edge to the other. Swimming is an educational process that has its teaching-learning space, and the classroom is the swimming pool; the body does not need to be “stuck” to desks, and attention is not only on the teacher. Inside the water, you need to focus on yourself and your movements; otherwise, the student sinks, drowns, or stays put. Looking at Swimming through the lens of complex thinking makes it possible to see it beyond the macrophysical level, the level of what is visible or perceived by the five senses. Being in contact with water is a moment of opening the conscience to creativity and intuition, of connection with the sacred and the human essence.